2017
DOI: 10.9734/arjass/2017/33164
|View full text |Cite
|
Sign up to set email alerts
|

Social Effects of Crude Oil Production Activities in Egbema, Imo State, Nigeria

Abstract: Literature abounds on the economic and environmental effects of crude oil production activities in the oil producing communities of Nigeria. Some of these effects include reduction in economic and agricultural activities due to oil spillage and gas flaring as well as health challenges. While efforts are being made to curtail some of these problems, sufficient attention has not been paid in published literature to the social dimension of crude oil production in Nigeria. This study thus sets out to assess social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Ihenetu et al (2017) observed high levels of heavy metals and physicochemical parameters in soil samples collected from five locations in Ohaji/Egbema. Osumgborogwu et al (2017) studied the effects of oil production on social activities in Egbema and concluded that despite the decline in economic activities, social activities were largely intact. No study was found on the impact of petroleum exploration on the environment in Ogbaru LGA.…”
Section: Introductionmentioning
confidence: 99%
“…Ihenetu et al (2017) observed high levels of heavy metals and physicochemical parameters in soil samples collected from five locations in Ohaji/Egbema. Osumgborogwu et al (2017) studied the effects of oil production on social activities in Egbema and concluded that despite the decline in economic activities, social activities were largely intact. No study was found on the impact of petroleum exploration on the environment in Ogbaru LGA.…”
Section: Introductionmentioning
confidence: 99%